PENGARUH MIND MAPPING TERHADAP PENGETAHUAN KESEHATAN GIGI DAN MULUT MURID KELAS V SD MESJID LHEU KEC. DARUL IMARAH KABUPATEN ACEH BESAR - Elfi Zahara; Nia Kurniawati; Sisca Mardelita; Mufizarni Mufizarni (Poltekkes Kemenkes Jambi, 2021)
Background: Dental and oral health education efforts that have been carried out so far are the lecture method, the learning method for brushing teeth and audio-visual and now it can be combined with the mind mapping method. This study aimed to determine the effect of mind mapping on dental and oral health knowledge of fifth grade students at SD Masjid Lheu, Kec. Darul Imarah, Aceh Besar District. Methods: This study was using a pre and post test design. 74 fifth grade students of SD Mesjid Lheu were taken using total sampling technique. The oral dental health intervention with the mind mapping method was carried out for 2 hours in the treatment group while the control group was not given any treatment. Subject knowledge was measured before and after treatment. Bivariate analysis was performed using a paired t test statistic. Results: There was a significant difference in students' knowledge before and after giving the mind mapping method (p=0.000). Significant difference also found between the treatment group and the control group (p=0.010) Conclusion: The use of the mind mapping method has an effect on the oral adn dental health knowledge in 5th grade students of SD Mesjid Lheu Aceh Besar